The Correlation Between Teachers’ Instructional Strategies and Students’ Academic (Skills) Achievement for Children with Special Needs in North Sulawesi - Mareike Seska Diana Lotulung; Anita Amelia Ole; Enlina Tumbelaka (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study investigates the extent of teachers’ instructional strategies, the level of students’ academic (skill) achievement, and the relationship between the two among children with special needs in special schools across North Sulawesi. Methodology: Employing a quantitative, descriptive-correlational research design, the study was conducted during the first semester of the 2023/2024 academic year. A total of 95 teacher respondents from 12 special education schools were selected through total population sampling. Data were collected using a validated Likert-scale questionnaire, and the results were analyzed using correlation analysis to determine the strength and significance of the relationship between instructional strategies and student achievement. Main Findings: Findings reveal that teachers demonstrate a consistently high level of instructional strategies. Specifically, the mean scores were as follows: understanding of students’ characteristics (M = 4.50), fulfilling roles as educators, instructors, mentors, and content deliverers (M = 4.57), and efforts in fostering creativity (M = 4.63). In terms of student academic (skill) achievement, the mean score was 4.46, suggesting a high level of learning outcomes among students with special needs. Most notably, the study found a statistically significant and strong correlation between teachers’ instructional strategies and students’ academic achievement, indicating that effective pedagogical approaches directly influence skill development in special education contexts. Novelty/Originality of this study: The novelty of this study lies in its focus on the nuanced relationship between instructional strategies and skill-based achievement within the under-researched demographic of special needs learners in Eastern Indonesia.